Exploring the relationship between food insecurity with hunger and academic progression at a large South African University - Wagner, F.; Kaneli, T.; Masango, M. (South African Journal of Higher Education, 2021)
Food insecurity has been recognized as one of the key challenges currently affecting students in higher education. However, there has been limited research in South African higher education that has sought to understand the relationship between food insecurity and student success. The current study defined student success as a student meeting the requirements to progress from one year of study to another. The study aimed to understand the relationship between food insecurity and student academic progression. Further to this, it aimed to understand the prevalence of food insecurity, and the characteristics of students most likely to progress. This study was carried out at a large South African university and targeted at the entire 2019 first-time, first year undergraduate student cohort (n=5 356). All eligible students were invited via email to participate in a self-administered, online cross-sectional survey. The Household Food Insecurity Access Scale (HFIAS) was used to measure student food insecurity. Data were linked to the end of the year academic progress outcomes, which indicated whether or not students had met the requirements to progress to the following year of study. The survey was completed by 1 612 students, giving a 30 per cent response rate. Overall, nearly a quarter of the students (23%) were found to be experiencing food insecurity with hunger, with 5 per cent experiencing severe hunger. A retention rate of 94 per cent was recorded, and a little over 70 per cent of participants progressed to the second year of study. Student academic progression was found to be significantly associated with food security status (p<0.001), as well as first generation status (p=0.007) and home location (p<0.001) in the bivariate analysis. Further to this, a multivariate analysis revealed that students experiencing little to no hunger were almost twice as likely to progress to the next year of study when compared to those experiencing food insecurity with hunger (Odds Ratio [OR]=1.876; 95% Confidence Interval [CI]: 1.454-2.418; p<0.001). The results of this study demonstrated that food insecurity with hunger was negatively associated with student academic progression. This is one of the first, and largest, South African studies to demonstrate this relationship. This work advocates for students experiencing food insecurity with hunger to be prioritised in university student support programmes, such as food security interventions, as this may improve student success.